MAQÂSHID AL-SYARI’AH (Wacana Pengantar Studi) Imam Muhardinata - Muhardinata, Imam (STAI Serdang Lubuk Pakam, 2019)
Since the time of the Prophet Muhammad, Maqâshid al-Shari'ah has be-come a consideration as a basis in establishing the law. Such efforts, then car-ried out also by the friends. Such efforts are clearly seen in several legal provi-sions carried out by Umar Ibn al-Khattab r.a. This Maqâshid al-Syar'iah study then gained a place in the science of usul al-fiqh, which was developed by the ushul in the application of qiyas, when talking about masalik al-Illah. Such studies are seen in several works of ushul al-fiqh, such as Ghiyas al-Umam fi Iltiyas al-Zulam with the concept of the term al-Masalih al-'Ammah by Abdul Malik al-Juwayni, one of the early contributors to the Maqâshid al-Shari'ah theory, ar-Risalah by al-Shafi'i, Al-Mustasfa by al-Ghazali, al-Mu'tamad by Abu al-Hasan al-Bashri, and others. This study was then developed broadly and systematically by Abu Ishaq al-Syathibi who later called his name al-Syathibi or as-Syathibi. In its continuation, Maqâshid al-Syari’ah has instead become a discussion that is less popular or even ignored in many reference books that talk about usul al-fiqh. The search for the topic of Maqâshid al-Shari'ah is not easy to obtain. So far the discussion of Maqâshid al-Shari'ah has been more identified with Abu Ishaq al-Syathibi or as-Syathibi. At least the books of usul al- fiqh salaf, especially those of the Islamic scholars of as-Syafi'i who discussed Maqâshid al-Shari'ah or even ignored them in their subject matter, were due to the relevance of this discussion to the theol-ogy which he believed. This debate about Maqâshid al-Shari'ah is not only relat-ed to theology, but also related to the success of Maqâshid al-Shari'ah as a source of legal development. The methods of developing Islamic law based on Maqâshid al-Shariah such as istihsan and mashlahah al-mursalah are disputed development methods.